2019
DOI: 10.1136/bcr-2019-231900
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium mucogenicumskin and soft tissue infection of the breast mimicking idiopathic granulomatous mastitis

Abstract: We present a case of a 28-year-old woman who came to medical attention after noticing a breast mass associated with an overlying eroded plaque of the skin. A core biopsy of the breast mass was negative for malignancy but demonstrated granulomatous inflammatory changes. Acid-fast bacilli and Gomori methenamine-silver stains were negative for microorganisms. The patient was diagnosed with presumptive idiopathic granulomatous mastitis and started on oral steroids. Her symptoms progressed. Tissue culture from a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
2
1
Order By: Relevance
“…Furthermore, differential diagnoses of GLM include plasma cell mastitis, duct ectasia, sclerosing lymphocytic lobular mastitis, IgG4-related sclerosing mastitis, and other known causes of granulomatous diseases such as tuberculosis, sarcoidosis, fat necrosis, foreign body granuloma, etc. [32,33]. However, in our study, we found that CD3-positive T lymphocytes were present at higher levels than CD20-positive B lymphocytes around vacuoles or microabscesses.…”
Section: Discussioncontrasting
confidence: 67%
“…Furthermore, differential diagnoses of GLM include plasma cell mastitis, duct ectasia, sclerosing lymphocytic lobular mastitis, IgG4-related sclerosing mastitis, and other known causes of granulomatous diseases such as tuberculosis, sarcoidosis, fat necrosis, foreign body granuloma, etc. [32,33]. However, in our study, we found that CD3-positive T lymphocytes were present at higher levels than CD20-positive B lymphocytes around vacuoles or microabscesses.…”
Section: Discussioncontrasting
confidence: 67%
“…A fine needle aspiration culture of the abscess in a female patient with IGM revealed Enterococcus avium ( 88 ). Tissue culture from a repeat biopsy in a 28-year-old woman grew Mycobacterium mucogenicum , a rare cause of skin and soft tissue infections ( 89 ). As a possible infectious etiology, Corynebacterium species ( 90 ), especially Corynebacterium kroppenstedtii ( 91 , 92 ) , have been identified in the progression of IGM.…”
Section: Triggering Events and Precipitating Factors Of Igmmentioning
confidence: 99%
“…Their isolation may be considered clinically important because RGMs are recovered from various environmental sources, including water, and they survive by forming biofilms and by interacting with protozoa [ 6 , 7 ]. After Mmuc was first reported as a Mycobacterium chelonae -like organism (MCLO) in a peritonitis outbreak in 1982, Mmuc strains have been detected in a wide range of infection sites, such as the central nervous system, skin, and lungs [ 8 , 9 , 10 ]. In particular, the most clinically significant infections are posttraumatic wound infections and catheter-related sepsis [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%